2011
DOI: 10.1103/physrevlett.106.134503
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Superlayer at the Turbulence Boundary

Abstract: In this Letter we present results from particle tracking velocimetry and direct numerical simulation that are congruent with the existence of a laminar superlayer, as proposed in the pioneering work of Corrsin and Kistler (NACA, Technical Report No. 1244, 1955). We find that the local superlayer velocity is dominated by a viscous component and its magnitude is comparable to the characteristic velocity of the smallest scales of motion. This slow viscous process involves a large surface area so that the global r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
146
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(166 citation statements)
references
References 18 publications
20
146
0
Order By: Relevance
“…The magnitudes of the velocity differences (u c − u), (v c − v) and (w c − w) are comparable to the Kolmogorov velocity scale, 0.013U e at the present height in the boundary layer, or u τ = 0.041U e . This observation seems consistent with the work of Holzner & Lüthi (2011), who considered the velocity of the turbulent non-turbulent interface relative to the local flow velocity. Like the present vortical structures, this interface is associated with small-scale turbulent motions (Westerweel et al 2009), and it typically moves at speeds of the order of the Kolmogorov velocity scale relative to the local flow velocity (Holzner & Lüthi 2011).…”
Section: Dispersion Of Vortices 41 Convection Of Individual Vorticessupporting
confidence: 81%
“…The magnitudes of the velocity differences (u c − u), (v c − v) and (w c − w) are comparable to the Kolmogorov velocity scale, 0.013U e at the present height in the boundary layer, or u τ = 0.041U e . This observation seems consistent with the work of Holzner & Lüthi (2011), who considered the velocity of the turbulent non-turbulent interface relative to the local flow velocity. Like the present vortical structures, this interface is associated with small-scale turbulent motions (Westerweel et al 2009), and it typically moves at speeds of the order of the Kolmogorov velocity scale relative to the local flow velocity (Holzner & Lüthi 2011).…”
Section: Dispersion Of Vortices 41 Convection Of Individual Vorticessupporting
confidence: 81%
“…locally occurring at the interface between turbulent and surrounding flow. It has been demonstrated recently that E can be understood from small-scale processes [6,10,11] since the global entrainment comes about through small scale viscous diffusion of vorticity that is augmented by the strongly convoluted interface separating turbulent from surrounding flow regions. However, our advancements in the understanding of the turbulent/ nonturbulent interface (TNTI) have been mostly limited to flows without density contrast [12].…”
Section: Introductionmentioning
confidence: 99%
“…3 Turbulent entrainment has been recently studied in relation to the interfacial layer which separates turbulent from irrotational (non-turbulent) flow: the so-called turbulent/non-turbulent interface (TNTI). 4,5 The long-standing question of turbulent entrainment has been the understanding of what are the physical mechanisms causing it. Turbulent motions with wide range of scales have been observed near TNTIs, from small-scale eddies, which are statistically universal, to large-scale structures, which are flow dependent, while both small and large-scale motions are expected to contribute to the turbulent entrainment by nibbling and engulfment, respectively.…”
mentioning
confidence: 99%
“…6 As the turbulent entrainment takes place, irrotational fluid crosses the TNTI due to some mechanism. The TNTI is often detected using a constant vorticity magnitude isosurface, 6 and for this reason turbulent entrainment has been investigated by analyzing this isosurface propagation, whose velocity is of the order of the Kolmogorov velocity v η ≡ (νε) 1/4 , reflecting the importance of small-scale features, 5 where ε is the dissipation rate of turbulent kinetic energy and ν is the kinematic viscosity. However, recent studies on the structure of TNTI showed that it displays a finite thickness, 7 consisting of two layers: the viscous superlayer (VSL) and the turbulent sublayer (TSL).…”
mentioning
confidence: 99%
See 1 more Smart Citation